Evaluation of clinical and radiographic outcome of friction fit conical abutment system in implant-supported dental prostheses: An in vivo study - Vineet Sharma; Jyoti Paliwal; Sumit Bhansali; Kamal Kumar Meena; Neha Gupta; Ashish Dadarwal (Wolters Kluwer Medknow Publications, 2022)
Aim: The purpose of this clinical study was to analyze the clinical feasibility of friction fit conical abutment system in implant-supported fixed dental prostheses as an alternative to cement and screw retention. Settings and Design: This was an in vivo longitudinal study. Materials and Methods: A total of 10 prostheses were designed as 3- or 4-unit fixed dental prostheses supported by two implants. All the subjects selected were evaluated for pocket probing depth (PPD) and marginal bone loss at the time of implant placement (T1), at the time of placement of friction fit prostheses (T2), and 12 months after placement of friction fit prostheses (T3). Marginal bone loss at T2 and T3 was measured with respect to bone levels at T1 and T2, respectively. The patient satisfaction was assessed at T2 and T3 using FDI clinical criteria and scoring system (modified by Monaco et al.). Statistical Analysis Used: Shapiro-Wilk test was employed to test the normality of data. Paired sample t-test was performed for quantitative variables. Results: A total of twenty implants were inserted in ten partially edentulous spaces; the average patient age was 50.2 years. No significant difference was seen between T2 and T3 for PPD. Comparison of marginal bone loss using paired t-test showed a statistically highly significant difference at T2 and T3 with higher value at T2. No prostheses were dislodged during postprosthetic follow-up. The survival rate was 100% for both the abutments and implants. No change in surface luster was observed 12 months following prosthetic rehabilitation in any case. No prostheses or framework fracture was reported and all patients were satisfied with the prosthesis received. Conclusions: Friction fit conical abutment system can act as a novel approach for the retention of implant-supported fixed dental prostheses.